Lack of collagen VIII reduces fibrosis and promotes early mortality and cardiac dilatation in pressure overload in mice†. (18th February 2015) - Skrbic, Biljana; Engebretsen, Kristin V.T.; Strand, Mari E.; Lunde, Ida G.; Herum, Kate M.; Marstein, Henriette S.; Sjaastad, Ivar; Lunde, Per K.; Carlson, Cathrine R.; Christensen, Geir; Bjørnstad, Johannes L.; Tønnessen, Theis
Abstract: Aims: In pressure overload, left ventricular (LV) dilatation is a key step in transition to heart failure (HF). We recently found that collagen VIII (colVIII), a non-fibrillar collagen and extracellular matrix constituent, was reduced in hearts of mice with HF and correlated to degree of dilatation. A reduction in colVIII might be involved in LV dilatation, and we here examined the role of reduced colVIII in pressure overload-induced remodelling using colVIII knock-out (col8KO) mice. Methods and results: Col8KO mice exhibited increased mortality 3–9 days after aortic banding (AB) and increased LV dilatation from day one after AB, compared with wild type (WT). LV dilatation remained increased over 56 days. Forty-eight hours after AB, LV expression of main structural collagens (I and III) was three-fold increased in WT mice, but these collagens were unaltered in the LV of col8KO mice together with reduced expression of the pro-fibrotic cytokine TGF-β, SMAD2 signalling, and the myofibroblast markers Pxn, α-SMA, and SM22. Six weeks after AB, LV collagen mRNA expression and protein were increased in col8KO mice, although less pronounced than in WT. In vitro, neonatal cardiac fibroblasts from col8KO mice showed lower expression of TGF-β, Pxn, α-SMA, and SM22 and reduced migratory ability possibly due to increased RhoA activity and reduced MMP2 expression. Stimulation with recombinant colVIIIα1 increased TGF-β expression and fibroblast migration. Conclusion: Lack of colVIII reduces myofibroblast differentiation and fibrosis and promotes early mortality and LV dilatation in response to pressure overload in mice.